Flame-retardant polymer solid-state electrolyte and preparation method and application thereof
Patent Information
- Application Number
- CN202611188298.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-13
AI Technical Summary
[0006]解决的技术问题:为解决现有聚合物固态电解质阻燃性能不足、室温离子电导率偏低以及机械强度难以有效抑制锂枝晶穿刺等问题,本发明提供一种以十溴二苯乙烷(DBDPE)作为阻燃填充材料的聚合物基固态电解质及其制备方法和应用,通过将十溴二苯乙烷均匀分散于聚合物基体中并与锂盐复配,能够在不显著牺牲离子传导能力的前提下有效提升电解质的阻燃等级和热稳定性,同时该填充组分有助于降低聚合物基体的结晶度,促进锂离子的均匀沉积并增强电解质膜的力学强度,从而改善固态电池的循环稳定性和倍率性能,为高安全锂固态电池的构建提供一种兼具阻燃特性和优良电化学综合性能的解决方案
[0016]有益效果:本发明以十溴二苯乙烷作为阻燃填充材料对聚合物固态电解质进行改性,在阻燃性能方面,十溴二苯乙烷在受热时能够释放溴自由基,中断气相燃烧链式反应。燃烧测试对比显示,未添加十溴二苯乙烷的聚合物电解质膜在接触火源后持续燃烧,而添加后的固态电解质膜在离开火源后能够迅速自熄,说明该材料有效提升了电解质的阻燃能力。同时,十溴二苯乙烷的引入并非简单扮演惰性填料的角色,其与聚合物基体和锂盐之间形成了协同配合关系。X射线衍射表征结果表明,十溴二苯乙烷的加入降低了PVDF-HFP或PEO的结晶度,聚合物分子链段的运动能力随之增强,有利于锂离子在聚合物基质中的迁移和传输,使改性电解质的离子电导率相对于未改性样品得到提升。所以,十溴二苯乙烷在发挥阻燃功能的同时,通过对聚合物聚集态结构的调控改善了离子传导环境,这与通常阻燃剂添加会稀释离子浓度、阻碍链段运动而劣化电化学性能的一般认识有所不同。在机械性能方面,均匀分散于聚合物基体中的十溴二苯乙烷微粒能够起到物理交联和刚性填充的作用,增强了电解质膜的力学强度,有助于抵抗锂枝晶的穿刺。电化学测试结果表明,采用该改性固态电解质组装的锂固态电池具有良好的可逆性和循环稳定性。扫描电子显微镜图像显示,所制备的电解质膜表面平整,十溴二苯乙烷各元素分布均匀,未出现团聚或相分离现象,这种均一的微观结构为电池长期稳定运行提供了基础。
Smart Images

Figure CN122907724A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical energy storage technology, specifically to the field of solid electrolyte technology, and particularly to a polymer-based solid electrolyte with added flame-retardant filler, its preparation method, and its application in lithium batteries. Background Technology
[0002] In recent years, lithium-ion batteries have been widely used in portable electronic devices, electric vehicles, and large-scale energy storage power stations due to their advantages such as high energy density and long cycle life. However, as demands for battery energy density and safety continue to increase, traditional liquid lithium-ion battery systems are facing increasingly severe challenges. On the one hand, liquid electrolytes using carbonate-based organic solvents are inherently flammable, easily leading to combustion or even explosion in the event of an internal short circuit or thermal runaway. On the other hand, the severe side reactions between the liquid electrolyte and the lithium metal anode remain difficult to resolve. These reactions not only lead to uncontrolled lithium dendrite growth, puncturing the separator and causing internal short circuits, but also result in the continuous decomposition and consumption of the electrolyte, severely impacting the battery's cycle life and coulombic efficiency. These safety hazards fundamentally limit the widespread application of lithium-ion batteries in higher energy density scenarios.
[0003] Solid-state batteries are considered one of the effective ways to solve the above problems. Their core idea is to use solid electrolytes to simultaneously replace the liquid electrolyte and polymer separator in traditional batteries, thereby simplifying the battery structure and fundamentally improving safety. Currently, research on solid-state electrolytes mainly revolves around three major technical routes: inorganic ceramic electrolytes such as oxide and sulfide systems, polymer solid-state electrolytes, and organic-inorganic composite electrolytes. Inorganic ceramic electrolytes have high ionic conductivity and excellent mechanical strength, but they are brittle, difficult to process, and have poor interfacial contact with electrodes. Polymer solid-state electrolytes, on the other hand, have attracted widespread attention due to their good flexibility, ease of processing into films, and good interfacial compatibility with electrodes. However, polymer solid-state electrolytes still face many technical bottlenecks in their practical application. The most prominent problems are manifested in three aspects: First, the room temperature ionic conductivity is generally low, typically only around 10... -4 -10 -5 The S / cm ratio is far from meeting the requirements of high-current charging and discharging at room temperature; secondly, the mechanical strength is insufficient, making it difficult to effectively suppress lithium dendrite puncture, and there is a risk of internal short circuit during long-term cycling; thirdly, the polymer skeleton itself is a flammable organic material, and although it does not contain liquid flammable solvents, there is still a risk of combustion under extreme thermal abuse conditions, which to some extent weakens the safety advantage of solid-state batteries compared to liquid batteries.
[0004] To address this, researchers have recently attempted to introduce flame retardants into polymer solid-state electrolyte systems to improve the thermal safety of materials without sacrificing electrochemical performance. An ideal flame-retardant strategy should not only impart self-extinguishing properties to the material but also avoid significant negative impacts on ion transport; ideally, it should simultaneously improve the mechanical properties and interfacial stability of the electrolyte. However, existing flame-retardant modification schemes often face a trade-off between flame-retardant efficiency and ionic conductivity. Some flame retardants added in large quantities can significantly dilute the lithium-ion concentration in the system, hindering polymer chain movement and leading to a substantial decrease in conductivity. Therefore, how to maintain or even optimize the ion transport capacity and electrochemical stability of the electrolyte while achieving good flame-retardant effects has become a critical problem that urgently needs to be solved in this field.
[0005] This invention is proposed against the backdrop of the aforementioned technology. By modifying polymer solid electrolytes with specific flame-retardant filler materials, it aims to improve safety performance while optimizing electrochemical performance, thus providing a feasible technical path for the development of high-performance solid-state batteries. Summary of the Invention
[0006] Technical Problem Solved: To address the shortcomings of existing polymer solid electrolytes, such as insufficient flame retardancy, low room temperature ionic conductivity, and difficulty in effectively suppressing lithium dendrite penetration due to mechanical strength issues, this invention provides a polymer-based solid electrolyte using decabromodiphenyl ethane (DBDPE) as a flame-retardant filler, along with its preparation method and applications. By uniformly dispersing DBDPE in a polymer matrix and compounding it with a lithium salt, the flame retardancy rating and thermal stability of the electrolyte can be effectively improved without significantly sacrificing ionic conductivity. Simultaneously, this filler component helps reduce the crystallinity of the polymer matrix, promotes uniform lithium ion deposition, and enhances the mechanical strength of the electrolyte membrane, thereby improving the cycle stability and rate performance of solid-state batteries. This provides a solution for constructing high-safety lithium solid-state batteries that combines flame retardant properties with excellent overall electrochemical performance.
[0007] Technical Solution: A method for preparing a flame-retardant polymer solid electrolyte, comprising the following steps: mixing a polymer, a lithium salt, and decabromodiphenyl ethane in an organic solvent to obtain a mixture, wherein the mass ratio of the polymer to the lithium salt is 3:2-4:1, the decabromodiphenyl ethane accounts for 1%-20% of the total mass of the solid electrolyte, and the polymer is at least one of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) and polyethylene oxide (PEO); forming a wet film from the mixture using a coating method or a casting method; placing the wet film in a vacuum drying oven and drying it at 50-200℃ to remove the organic solvent, thereby obtaining a solid electrolyte membrane.
[0008] The aforementioned decabromodiphenyl ethane accounts for 5% of the total mass of the solid electrolyte.
[0009] The lithium salt mentioned above is at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, and lithium bis(oxalatoborate).
[0010] The organic solvent mentioned above is at least one of N,N-dimethylformamide, acetonitrile, and N-methylpyrrolidone.
[0011] The drying time is 8-12 hours.
[0012] A flame-retardant polymer solid electrolyte is prepared by the above-described preparation method.
[0013] A lithium solid-state battery comprising the aforementioned flame-retardant polymer solid electrolyte.
[0014] The operating temperature of the above-mentioned batteries is 30-100℃.
[0015] The battery also contains a liquid electrolyte and operates at temperatures ranging from -30 to 100°C.
[0016] Beneficial Effects: This invention modifies polymer solid electrolytes using decabromodiphenyl ethane as a flame-retardant filler. Regarding flame retardancy, decabromodiphenyl ethane releases bromine free radicals upon heating, interrupting the gas-phase combustion chain reaction. Comparative combustion tests show that the polymer electrolyte membrane without added decabromodiphenyl ethane continues to burn after contact with a flame source, while the solid electrolyte membrane with added decabromodiphenyl ethane self-extinguishes rapidly after leaving the flame source, indicating that this material effectively improves the flame retardancy of the electrolyte. Furthermore, the introduction of decabromodiphenyl ethane does not simply act as an inert filler; it forms a synergistic relationship with the polymer matrix and lithium salt. X-ray diffraction characterization results show that the addition of decabromodiphenyl ethane reduces the crystallinity of PVDF-HFP or PEO, thereby enhancing the mobility of polymer molecular chains, which is beneficial for the migration and transport of lithium ions in the polymer matrix, resulting in an increase in the ionic conductivity of the modified electrolyte compared to the unmodified sample. Therefore, while performing flame retardant functions, decabromodiphenyl ethane improves the ion conduction environment by regulating the polymer's aggregated structure. This differs from the common understanding that adding flame retardants dilutes ion concentration, hinders chain segment movement, and degrades electrochemical performance. In terms of mechanical properties, the decabromodiphenyl ethane particles uniformly dispersed in the polymer matrix act as physical cross-links and rigid fillers, enhancing the mechanical strength of the electrolyte membrane and helping to resist lithium dendrite penetration. Electrochemical test results show that lithium solid-state batteries assembled using this modified solid electrolyte exhibit good reversibility and cycle stability. Scanning electron microscopy images show that the prepared electrolyte membrane has a smooth surface, with uniform distribution of decabromodiphenyl ethane elements, and no agglomeration or phase separation. This uniform microstructure provides a foundation for the long-term stable operation of the battery. Attached Figure Description
[0017] Figure 1 The XRD patterns of PVDF-HFP, PVDF-HFP@LiTFSI, and PVDF-HFP@DBDPE are shown, with a test range of 5°–80°. The figures show that PVDF@DBDPE contains diffraction peaks of DBDPE, indicating successful incorporation of the material into the solid electrolyte. Furthermore, the DBDPE filler helps reduce the crystallinity of the PVDF-HFP polymer, significantly increasing the amorphous phase.
[0018] Figure 2 This is a SEM image and elemental mapping of PVDF-HFP@DBDPE. It shows that PVDF-HFP and LiTFSI elements are uniformly distributed within the solid electrolyte, while the Br element of DBDPE is distributed at the upper and lower interfaces of the solid electrolyte. Therefore, in this solid-state battery, the DBDPE flame retardant is distributed at the interface between the positive and negative electrodes and the PVDF-HFP@DBDPE solid electrolyte.
[0019] Figure 3 This is a SEM image and elemental mapping of PEO@DBDPE. It shows that PEO, LiTFSI, and DBDPE are uniformly distributed in the PEO@DBDPE solid electrolyte.
[0020] Figure 4 The first-cycle charge-discharge curves of PVDF-HFP@DBDPE electrolyte membranes with different proportions and pure PVDF-HFP without DBDPE are shown at a current density of 0.1 C. It can be seen that PVDF, PVDF-HFP@1%DBDPE, PVDF-HFP@3%DBDPE, PVDF-HFP@5%DBDPE, and PVDF-HFP@10%DBDPE, along with LiNi... 0.8 Co 0.1 Mn 0.1 The initial charge capacities of the metal batteries with O2 (NCM811) cathode were 183.4, 185.3, 185.6, 195.4, and 181.9 mAh / g, respectively, and the initial discharge capacities were 157.3, 157.4, 158.6, 172, and 154.9 mAh / g, respectively. The electrochemical performance was best with 5% DBDPE filler.
[0021] Figure 5 For comparison of the ionic conductivity performance of electrolyte membranes in some embodiments, the conductivity of the PVDF-HFP and PEO solid electrolyte examples is 3×10⁻⁶. -3 and 9×10 -4 The conductivity was reduced to S / cm, while the addition of DBDPE increased the ionic conductivity to 3.5 × 10⁻⁶. -3 and 1×10 -3S / cm. It can be seen that the lithium-ion conductivity is highest in the PVDF-HFP@DBDPE solid electrolyte membrane.
[0022] Figure 6 Electrochemical window curves for PVDF@DBDPE with different proportions are shown, with the 5% DBDPE filler having the widest electrochemical window.
[0023] Figure 7 This is a comparative flame retardancy test between PVDF-HFP and PVDF-HFP@DBDPE. The PVDF-HFP solid electrolyte is extremely flammable and eventually burns completely. In contrast, PVDF-HFP@DBDPE cannot burn even under flame; the electrolyte extinguishes immediately upon removal of the flame, indicating that the electrolyte membrane with added DBDPE possesses excellent flame retardant properties. Detailed Implementation
[0024] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] Furthermore, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0026] DBDPE: Decabromodiphenyl ethane;
[0027] PVDF-HFP: Polyvinylidene fluoride-hexafluoropropylene copolymer;
[0028] PEO: Polyethylene oxide;
[0029] DMF: N,N-dimethylformamide;
[0030] NMP: N-methylpyrrolidone;
[0031] LiTFSI: Lithium bis(trifluoromethanesulfonyl)imide;
[0032] LiFSI: Lithium difluorosulfonylimide;
[0033] LiPF6: Lithium hexafluorophosphate;
[0034] LiBOB: Lithium dioxalatoborate.
[0035] Example 1
[0036] PVDF-HFP and LiTFSI were added to DMF solvent at a mass ratio of 3:2, and 1% (by mass) of flame-retardant filler DBDPE (equivalent to PVDF-HFP) was added. The mixture was stirred at 600 rpm for 8 hours at room temperature until homogeneous. The solution was then uniformly coated onto a clean glass plate, with a wet film thickness of approximately 0.09 mm. The film was then dried in a vacuum oven at -30 MPa at 80 °C for 12 hours. After drying to remove the solvent, the film was cut into 19 mm diameter pieces to obtain the PVDF-HFP@DBDPE solid electrolyte membrane. A lithium sheet was used as the negative electrode, and NCM811 as the positive electrode. The prepared electrolyte was placed in between, and 10 μL of lithium electrolyte was added dropwise to wet the electrolyte. The solid-state battery was assembled in an argon-atmosphere glove box, and electrochemical tests were performed at room temperature using a Newway battery testing system. The initial charge capacity of the solid-state lithium metal battery composed of NCM811 was 185.3 mAh / g, and the initial discharge capacity was 157.4 mAh / g. A solid-state battery was assembled in an argon-atmosphere glove box using lithium sheets on the positive electrode side and stainless steel sheets on the negative electrode side. The LSV was tested at room temperature on an electrochemical workstation, and the electrochemical window was approximately 3.9 V.
[0037] Example 2
[0038] PVDF-HFP and LiTFSI were added to DMF solvent at a mass ratio of 3:2, and 3% (by mass) of flame-retardant filler DBDPE (equivalent to PVDF-HFP) was added. The mixture was stirred at 600 rpm for 8 hours at room temperature until homogeneous. The solution was then uniformly coated onto a clean glass plate, with a wet film thickness of approximately 0.09 mm. The film was then dried in a vacuum oven at -30 MPa at 80 °C for 12 hours. After drying to remove the solvent, the film was cut into 19 mm diameter pieces to obtain the PVDF-HFP@DBDPE solid electrolyte membrane. A lithium sheet was used as the negative electrode, and NCM811 as the positive electrode. The prepared electrolyte was placed in between, and 10 μL of lithium electrolyte was added dropwise to wet the electrolyte. The solid-state battery was assembled in an argon-atmosphere glove box, and electrochemical tests were performed at room temperature using a Newway battery testing system. The initial charge capacity of the solid-state lithium metal battery composed of NCM811 was 185.6 mAh / g, and the initial discharge capacity was 158.6 mAh / g. A solid-state battery was assembled in an argon-atmosphere glove box using lithium sheets on the positive electrode side and stainless steel sheets on the negative electrode side. The LSV was tested at room temperature on an electrochemical workstation, and the electrochemical window was approximately 4.4 V.
[0039] Example 3
[0040] PVDF-HFP and LiTFSI were added to DMF solvent at a mass ratio of 3:2, along with 5% (by mass) of flame-retardant filler DBDPE from PVDF-HFP. The mixture was stirred at 600 rpm for 8 hours at room temperature until homogeneous. The solution was then uniformly coated onto a clean glass plate, resulting in a wet film thickness of approximately 0.09 mm. The film was then dried in a vacuum oven at -30 MPa at 80 °C for 12 hours. After drying to remove the solvent, the film was cut into 19 mm diameter pieces to obtain the PVDF-HFP@DBDPE solid electrolyte membrane. A lithium sheet was used as the negative electrode, and NCM811 was used as the positive electrode. The prepared electrolyte was placed in between, and 10 μL of lithium electrolyte was added dropwise to wet the electrolyte. The solid-state battery was assembled in an argon-atmosphere glove box, and its ionic conductivity was tested on an electrochemical workstation at 25–80 °C. The lithium-ion conductivity was 3.5 × 10⁻⁶. -3 The S / cm of the solid-state lithium metal battery, when combined with NMC811, yielded an initial charge capacity of 195.4 mAh / g and an initial discharge capacity of 172 mAh / g. The solid-state battery was assembled in an argon-atmosphere glove box using a lithium sheet as the positive electrode and a stainless steel sheet as the negative electrode. LSV testing was performed at room temperature on an electrochemical workstation, revealing an electrochemical window of approximately 4.5V.
[0041] Example 4
[0042] PVDF-HFP and LiTFSI were added to DMF solvent at a mass ratio of 3:2, and 10% (by mass) of flame-retardant filler DBDPE (equivalent to PVDF-HFP) was added. The mixture was stirred at 600 rpm for 8 hours at room temperature until homogeneous. The solution was then uniformly coated onto a clean glass plate, with a wet film thickness of approximately 0.09 mm. The film was then dried in a vacuum oven at -30 MPa at 80 °C for 12 hours. After drying to remove the solvent, the film was cut into 19 mm diameter pieces to obtain the PVDF-HFP@DBDPE solid electrolyte membrane. A lithium sheet was used as the negative electrode, and NCM811 as the positive electrode. The prepared electrolyte was placed in between, and 10 μL of lithium electrolyte was added dropwise to wet the electrolyte. The solid-state battery was assembled in an argon-atmosphere glove box, and electrochemical tests were performed using a Newway battery testing system. The initial charge capacity of the solid-state lithium metal battery composed of NCM811 was 181.9 mAh / g, and the initial discharge capacity was 154.9 mAh / g. A solid-state battery was assembled in an argon-atmosphere glove box using lithium sheets on the positive electrode side and stainless steel sheets on the negative electrode side. The LSV was tested at room temperature on an electrochemical workstation, and the electrochemical window was approximately 4.3 V.
[0043] Example 5
[0044] PVDF-HFP and LiTFSI were added to DMF solvent at a mass ratio of 4:1, along with 5% (by mass) of flame-retardant filler DBDPE from PVDF-HFP. The mixture was stirred at 600 rpm for 8 hours at room temperature until homogeneous. Afterward, it was vacuum-dried in a vacuum oven at room temperature for 120 minutes, poured into a PTFE mold (8 cm long, 6 cm wide), and allowed to stand at room temperature for 12 hours. Then, it was dried in a vacuum oven at 50 °C for 12 hours. After drying to remove the solvent, the film was cut into 19 mm diameter pieces to obtain the PVDF-HFP@DBDPE solid electrolyte membrane. A lithium sheet was used as the negative electrode, and NCM811 as the positive electrode. The prepared electrolyte was placed in between, and 10 μL of lithium electrolyte was added dropwise to wet the electrolyte. The solid-state battery was assembled in an argon-atmosphere glove box, and electrochemical tests were performed using a Newway battery testing system.
[0045] Example 6
[0046] PVDF-HFP and LiFSI were added to DMF solvent at a mass ratio of 3:2, and 5% (by mass) of flame-retardant filler DBDPE (equivalent to PVDF-HFP) was added. The mixture was stirred at 600 rpm for 8 hours at room temperature until homogeneous. The solution was then uniformly coated onto a clean glass plate, with a wet film thickness of approximately 0.09 mm. The plate was then dried in a vacuum oven at -30 MPa at 80 °C for 12 hours. After drying, the film was cut into 19 mm diameter pieces to obtain the PVDF-HFP@DBDPE solid electrolyte membrane. A lithium sheet was used as the negative electrode, and NCM811 was used as the positive electrode. The prepared electrolyte was placed in between, and 10 μL of lithium electrolyte was added dropwise to wet the electrolyte. The solid-state battery was assembled in an argon-atmosphere glove box, and electrochemical tests were performed using a Newway battery testing system.
[0047] Example 7
[0048] PVDF-HFP and LiFSI were added to DMF solvent at a mass ratio of 3:2, along with 5% (by mass) of flame-retardant DBDPE material. The mixture was stirred at 600 rpm for 8 hours at room temperature until homogeneous. Afterward, it was vacuum-dried in a vacuum oven at room temperature for 120 minutes, poured into a PTFE mold (8 cm long, 6 cm wide), and allowed to stand at room temperature for 12 hours. Then, it was dried in a vacuum oven at 50 °C for 12 hours. After drying, the film was cut into 19 mm diameter pieces to obtain the PVDF-HFP@DBDPE solid electrolyte membrane. A lithium sheet was used as the negative electrode, and NCM811 as the positive electrode. The prepared electrolyte was placed in the middle, and 10 μL of lithium electrolyte was added dropwise to wet the electrolyte. The solid-state battery was assembled in an argon-atmosphere glove box, and electrochemical tests were performed using a Newway battery testing system.
[0049] Example 8
[0050] PVDF-HFP and LiPF6 were added to DMF solvent at a mass ratio of 3:2, along with 5% (by mass) of flame-retardant DBDPE material. The mixture was stirred at 600 rpm for 8 hours at room temperature until homogeneous. The solution was then uniformly coated onto a clean glass plate, resulting in a wet film thickness of approximately 0.09 mm. The film was then dried in a vacuum oven at -30 MPa at 80 °C for 12 hours. After solvent drying, the film was cut into 19 mm diameter pieces to obtain the PVDF-HFP@DBDPE solid electrolyte membrane. A lithium sheet was used as the negative electrode, and NCM811 as the positive electrode. The prepared electrolyte was placed in between, and 10 μL of lithium electrolyte was added dropwise to wet the electrolyte. The solid-state battery was assembled in an argon-atmosphere glove box, and electrochemical tests were performed using a Newway battery testing system.
[0051] Example 9
[0052] PVDF-HFP and LiPF6 were added to DMF solvent at a mass ratio of 3:2, and 5% (by mass) of flame-retardant DBDPE material was added. The mixture was stirred at 600 rpm for 8 hours at room temperature until homogeneous. Afterward, the mixture was vacuum-dried in a vacuum oven at room temperature for 120 minutes, poured into a PTFE mold (8 cm long, 6 cm wide), and allowed to stand at room temperature for 12 hours. Then, it was dried in a vacuum oven at 50 °C for 12 hours. After drying, the film was cut into 19 mm diameter pieces to obtain the PVDF-HFP@DBDPE solid electrolyte membrane. A lithium sheet was used as the negative electrode, and NCM811 as the positive electrode. The prepared electrolyte was placed in the middle, and 10 μL of lithium electrolyte was added dropwise to wet the electrolyte. The solid-state battery was assembled in an argon-atmosphere glove box, and electrochemical tests were performed using a Newway battery testing system.
[0053] Example 10
[0054] PVDF-HFP and LiBOB were added to DMF solvent at a mass ratio of 3:2, along with 5% (by mass) of flame-retardant DBDPE material. The mixture was stirred at 600 rpm for 8 hours at room temperature until homogeneous. The solution was then uniformly coated onto a clean glass plate, resulting in a wet film thickness of approximately 0.09 mm. The film was then dried in a -30 MPa vacuum oven at 80 °C for 12 hours. After drying, the film was cut into 19 mm diameter pieces to obtain the PVDF-HFP@DBDPE solid electrolyte membrane. A lithium sheet was used as the negative electrode, and NCM811 was used as the positive electrode. The prepared electrolyte was placed in between, and 10 μL of lithium electrolyte was added dropwise to wet the electrolyte. The solid-state battery was assembled in an argon-atmosphere glove box, and electrochemical tests were performed using a Newway battery testing system.
[0055] Example 11
[0056] PVDF-HFP and LiBOB were added to DMF solvent at a mass ratio of 3:2, along with 5% (by mass) of flame-retardant DBDPE material. The mixture was stirred at 600 rpm for 8 hours at room temperature until homogeneous. Afterward, it was vacuum-dried in a vacuum oven at room temperature for 120 minutes, poured into a PTFE mold (8 cm long, 6 cm wide), and allowed to stand at room temperature for 12 hours. Then, it was dried in a vacuum oven at 50 °C for 12 hours. After drying the solvent, the film was cut into 19 mm diameter pieces to obtain the PVDF-HFP@DBDPE solid electrolyte membrane. A lithium sheet was used as the negative electrode, and NCM811 as the positive electrode. The prepared electrolyte was placed in the middle, and 10 μL of lithium electrolyte was added dropwise to wet the electrolyte. The solid-state battery was assembled in an argon-atmosphere glove box, and electrochemical tests were performed using a Newway battery testing system.
[0057] Example 12
[0058] PEO and LiTFSI were added to DMF solvent at a mass ratio of 3:2, along with 5% (by mass) of flame-retardant DBDPE. The mixture was stirred at 600 rpm for 8 hours at room temperature until homogeneous. The solution was then uniformly coated onto a clean glass plate, resulting in a wet film thickness of approximately 0.09 mm. The film was then dried in a vacuum oven at -30 MPa at 80 °C for 12 hours. After solvent drying, the film was cut into 19 mm diameter pieces to obtain the PEO@DBDPE solid electrolyte membrane. A lithium sheet was used as the negative electrode, and NCM811 was used as the positive electrode. The prepared electrolyte was placed in between, and 10 μL of lithium electrolyte was added dropwise to wet the electrolyte. The solid-state battery was assembled in an argon-atmosphere glove box, and electrochemical tests were performed using a Newway battery testing system.
[0059] Example 13
[0060] PEO and LiTFSI were added to DMF solvent at a mass ratio of 3:2, along with 5% (by mass) of flame-retardant DBDPE. The mixture was stirred at 600 rpm for 8 hours at room temperature until homogeneous. Afterward, it was vacuum-dried in a vacuum oven at room temperature for 120 minutes, poured into a polytetrafluoroethylene mold (8 cm long, 6 cm wide), and allowed to stand at room temperature for 12 hours. Then, it was dried in a vacuum oven at 50 °C for 12 hours. After drying, the film was cut into 19 mm diameter pieces to obtain the PEO@DBDPE solid electrolyte membrane. A lithium sheet was used as the negative electrode, and NCM811 as the positive electrode. The prepared electrolyte was placed in the middle, and 10 μL of lithium electrolyte was added dropwise to wet the electrolyte. The solid-state battery was assembled in an argon-atmosphere glove box, and electrochemical tests were performed using a Newway battery testing system.
[0061] Example 14
[0062] PEO and LiFSI were added to DMF solvent at a mass ratio of 3:2, along with 5% (by mass) of flame-retardant DBDPE. The mixture was stirred at 600 rpm for 8 hours at room temperature until homogeneous. The solution was then uniformly coated onto a clean glass plate, resulting in a wet film thickness of approximately 0.09 mm. The film was then dried in a -30 MPa vacuum oven at 80 °C for 12 hours. After drying, the film was cut into 19 mm diameter pieces to obtain the PEO@DBDPE solid electrolyte membrane. A lithium sheet was used as the negative electrode, and NCM811 was used as the positive electrode. The prepared electrolyte was placed in between, and 10 μL of lithium electrolyte was added dropwise to wet the electrolyte. The solid-state battery was assembled in an argon-atmosphere glove box, and electrochemical tests were performed using a Newway battery testing system.
[0063] Example 15
[0064] PEO and LiFSI were added to DMF solvent at a mass ratio of 3:2, and 5% (by mass) of flame-retardant DBDPE material was added. The mixture was stirred at 600 rpm for 8 hours at room temperature until homogeneous. Afterward, the mixture was vacuum-dried in a vacuum oven at room temperature for 120 minutes, poured into a polytetrafluoroethylene mold (8 cm long, 6 cm wide), and allowed to stand at room temperature for 12 hours. Then, it was dried in a vacuum oven at 50 °C for 12 hours. After drying the solvent, the film was cut into 19 mm diameter pieces to obtain the PEO@DBDPE solid electrolyte membrane. A lithium sheet was used as the negative electrode, and NCM811 was used as the positive electrode. The prepared electrolyte was placed in the middle, and 10 μL of lithium electrolyte was added dropwise to wet the electrolyte. The solid-state battery was assembled in an argon-atmosphere glove box, and electrochemical tests were performed on the Xinwei Battery Testing System.
[0065] Example 16
[0066] PEO and LiPF6 were added to DMF solvent at a mass ratio of 3:2, and 5% (by mass) of flame-retardant DBDPE material was added. The mixture was stirred at 600 rpm for 8 hours at room temperature until homogeneous. The solution was then uniformly coated onto a clean glass plate, with a wet film thickness of approximately 0.09 mm. The plate was then dried in a vacuum oven at -30 MPa at 80 °C for 12 hours. After drying, the film was cut into 19 mm diameter pieces to obtain the PEO@DBDPE solid electrolyte membrane. A lithium sheet was used as the negative electrode, and NCM811 was used as the positive electrode. The prepared electrolyte was placed in between, and 10 μL of lithium electrolyte was added dropwise to wet the electrolyte. The solid-state battery was assembled in an argon-atmosphere glove box, and electrochemical tests were performed using a Newway battery testing system.
[0067] Example 17
[0068] PEO and LiPF6 were added to DMF solvent at a mass ratio of 3:2, followed by 5% of the flame-retardant material DBDPE (based on the mass of PEO). The mixture was stirred at 600 rpm for 8 hours at room temperature until homogeneous. Afterward, it was vacuum-dried in a vacuum oven at room temperature for 120 minutes, poured into a polytetrafluoroethylene mold (8 cm long, 6 cm wide), and allowed to stand at room temperature for 12 hours. Then, it was dried in a vacuum oven at 50 °C for 12 hours. Finally, the dried film was cut into 19 mm diameter pieces to obtain the PEO@DBDPE solid electrolyte membrane. A lithium sheet was used as the negative electrode, NCM811 as the positive electrode, and the prepared electrolyte was placed in between. 10 μL of lithium electrolyte was added dropwise to wet the electrolyte. The solid-state battery was assembled in an argon-atmosphere glove box, and electrochemical tests were performed using a Newway battery testing system.
[0069] Example 18
[0070] PEO and LiBOB were added to DMF solvent at a mass ratio of 3:2, along with 5% (by mass of PEO) of the flame-retardant material DBDPE. The mixture was stirred at 600 rpm for 8 hours at room temperature until homogeneous. The solution was then uniformly coated onto a clean glass plate, resulting in a wet film thickness of approximately 0.09 mm. The film was then dried in a vacuum oven at -30 MPa at 80 °C for 12 hours. After solvent drying, the film was cut into 19 mm diameter pieces to obtain the PEO@DBDPE solid electrolyte membrane. A lithium sheet was used as the negative electrode, and NCM811 was used as the positive electrode. The prepared electrolyte was placed in between, and 10 μL of lithium electrolyte was added dropwise to wet the electrolyte. The solid-state battery was assembled in an argon-atmosphere glove box, and electrochemical tests were performed using a Newway battery testing system.
[0071] Example 19
[0072] PEO and LiBOB were added to DMF solvent at a mass ratio of 3:2, along with 5% (by mass of PEO) of the flame-retardant material DBDPE. The mixture was stirred at 600 rpm for 8 hours at room temperature until homogeneous. Afterward, it was vacuum-dried in a vacuum oven at room temperature for 120 minutes, poured into a polytetrafluoroethylene mold (8 cm long, 6 cm wide), and allowed to stand at room temperature for 12 hours. Then, it was dried in a vacuum oven at 50 °C for 12 hours. After drying, the film was cut into 19 mm diameter pieces to obtain the PEO@DBDPE solid electrolyte membrane. A lithium sheet was used as the negative electrode, NCM811 as the positive electrode, and the prepared electrolyte was placed in between. 10 μL of lithium electrolyte was added dropwise to wet the electrolyte. The solid-state battery was assembled in an argon-atmosphere glove box, and electrochemical tests were performed using a Newway battery testing system.
[0073] Application and effect verification:
[0074] Using an NCM811 electrode as the positive electrode and a lithium sheet as the negative electrode, an electrolyte made of PVDF@5%DBDPE (as in Example 1) was used to replace the commonly used lithium battery separator. The battery was assembled in an argon-filled glove box. Charge-discharge tests of the lithium-ion battery were performed using the Xinwei Battery Testing System. XRD characterization showed that the synthesized PVDF-HFP@5%DBDPE contained DBDPE components, and the addition of DBDPE reduced the crystallinity of PVDF-HFP, improving the mobility of molecular chains. Figure 2 SEM images show that the PVDF-HFP@5%DBDPE electrolyte membrane surface is smooth, without obvious depressions or protrusions. Br element is uniformly distributed on both the upper and lower surfaces of the solid electrolyte, indicating that DBDPE is mainly distributed on the surface of the PVDF-HFP@5%DBDPE electrolyte membrane. Figure 3 As shown, the charging and discharging voltage range is 2-4.2 V (vs. Li). + Under the conditions of / Li (Implementation Case 3), the initial charge capacity of PVDF-HFP@5%DBDPE is 195 mAh·g. -1 The initial discharge capacity is 172 mAh·g -1 . Figure 4 The results showed that the addition of DBDPE resulted in good flame retardant properties in the solid electrolyte, which was able to quickly stop combustion after the fire source was removed.
[0075] Although embodiments of the present invention have been described above, they are not limited to the applications set forth in the specification and embodiments, and can be used in various fields suitable for the present invention. Therefore, without departing from the claims and the general concept defined by their equivalents, the present invention is not limited to the specific detailed methods and the illustrations shown in this specification.
Claims
1. A method for preparing a flame-retardant polymer solid electrolyte, characterized in that, The process includes the following steps: mixing a polymer, a lithium salt, and decabromodiphenyl ethane in an organic solvent to obtain a mixture, wherein the mass ratio of the polymer to the lithium salt is 3:2-4:1, the decabromodiphenyl ethane accounts for 1%-20% of the total mass of the solid electrolyte, and the polymer is at least one of polyvinylidene fluoride-hexafluoropropylene copolymer and polyethylene oxide; forming a wet film from the mixture using a coating or casting method; placing the wet film in a vacuum drying oven and drying it at 50-200°C to remove the organic solvent, thereby obtaining a solid electrolyte membrane.
2. The preparation method according to claim 1, characterized in that, The decabromodiphenyl ethane accounts for 5% of the total mass of the solid electrolyte.
3. The preparation method according to claim 1, characterized in that, The lithium salt is at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, and lithium bis(oxalatoborate).
4. The preparation method according to claim 1, characterized in that, The organic solvent is at least one of N,N-dimethylformamide, acetonitrile, and N-methylpyrrolidone.
5. The preparation method according to claim 1, characterized in that, The drying time is 8-12 hours.
6. A flame-retardant polymer solid electrolyte, characterized in that, It is prepared by any one of claims 1-5.
7. A lithium solid-state battery comprising the flame-retardant polymer solid electrolyte of claim 6.
8. The lithium solid-state battery according to claim 8, characterized in that, The battery operates at a temperature of 30-100℃.
9. The lithium solid-state battery according to claim 8, characterized in that, The battery also contains a liquid electrolyte and operates at a temperature of -30 to 100°C.